The Role of Citizen Behavior in Strengthening National Resilience Amidst the Current of Globalization - Jevera Deron Krisanto; Suparmi (Kawakib: Journal of Multidisciplinary Research, 2026)
National defense awareness is a fundamental aspect in maintaining the nation's sustainability, especially amidst globalization and the development of digital technology. Basic values such as love for the homeland, national commitment, belief in Pancasila, readiness to sacrifice, and physical and mental abilities are key pillars that need to be instilled from an early age, especially in the younger generation. However, social change and the rapid flow of global information have influenced the character of society, resulting in various challenges, including the weakening of nationalism, the fading of local culture, and the increasing spread of ideologies that threaten the integrity of the state. This literature-based research examines strategies for strengthening national defense awareness through formal and non-formal education, internalization of Pancasila values, and increasing digital literacy as an effort to counter information manipulation, propaganda, and destructive content in the digital space. The study results indicate that character building, curriculum improvements, integration of digital literacy education, and cultivating positive behaviors that avoid bullying, sexual violence, intolerance, and corruption are strategic steps in developing the younger generation as agents of change. With an approach relevant to the needs of the modern era, national defense awareness is expected to grow sustainably to strengthen national resilience and safeguard national sovereignty.